Selection of comparative material as objective basis of expertise in forensic document examination - Kipouràs, Pàvlos (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
The comparative method is universally accepted and applied in forensic document examination. Comparing the questioned handwriting or signature against the comparative material reveals graphic elements which allow the expert to arrive at a technically and methodologically structured conclusion regarding authenticity. The opposing parties in a case provide comparative material for the expert to assess. Specimens deriving from public documents are initially considered to be of safe origin – these usually consist of signatures. However, handwriting samples are mainly found in private documents. Such circumstances make it easier for each party to contest the material provided by the opposite party while asserting the authenticity of their own. This, in turn, may lead to a debate between experts regarding the selection of appropriate comparative specimens. After all, the validity of their conclusions depends on whether the choice they make in this matter is correct. The present article provides some methodological guidelines, suggestions regarding the way of expressing the final expert opinion, as well as illustrates them through a specific case study.
Keywords: comparative material; signature; forgery; authenticity; public documents; private documents; handwriting; expert’s conclusion; methodological criteria